Denaturation of Protein Using Microcantilever Sensor - Xue, Changguo; Teng, Yanhua; Wu, Shangquan; Zhang, Qingchuan; Zhang, Mingxu (Asian Journal of Chemistry, 2012)
A real-time detection denaturation of the trypsin using microcantilever sensor platform with optical lever technique was reported. The trypsin was indirectly immobilized on the cantilever gold surface by thiol self-assembled monolayer and the activated carboxy group of the thiol by EDC/NHS. Consequently, the deflections of the microcantilever corresponding to the process of injecting different concentration of GuHCl were generated.